The Influence of Inventory Accounting Information Systems and Inventory Internal Control on the Effectiveness of Hospital Medicine Inventories - Diki Maulana; Ade Sudarma (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to determine the effect of inventory accounting information systems and inventory internal control on the effectiveness of partial and simultaneous hospital medical supplies, where the study was conducted at the Jampangkulon General Hospital, using quantitative research methods with parametric statistical approaches for data collection techniques using questionnaires, interviews, literature and documentation, the number of population and a sample of 33 was taken from the number of employees of the pharmacy installation of the Jampangkulon General Hospital. The data analysis technique used is validity test, reliability test, classical assumption test, multiple regression test, and hypothesis testing. This research is assisted by SPSS25 software by producing a conclusion that inventory accounting information systems and inventory internal control on inventory effectiveness can be said to have a positive and significant effect on the effectiveness of drug supplies in hospitals. Judging from the significance value obtained through the t-test and f-test of 0.00 <0.05, which means that H0 is rejected, H1 is accepted.